Analysis of implementation conditions under difficult geotechnical conditions using the SWOT analysis. Issue 1 (November 2019) - Gajzler, Marcin; Nowotarski, Piotr
Abstract: Difficult and complex geological conditions are often an obstacle to the efficient implementation of construction works related to the erection of objects, in particular, earthworks and foundations. In the event of an additional occurrence of adverse weather conditions, there may be a delay in the final effect of the work and exceeding the construction costs. The article presents the stage of the implementation case in which these factors were compiled. The SWOT analysis was an element helpful in analyzing the situation and also allowing to make decisions regarding implementation. Through this analysis, the contractor identified the possible activities, including opportunities and strengths, which allowed for the development of a scenario. This is important because the lack of action would cause even greater delays and financial losses than those already existing.